2019
DOI: 10.4324/9781315162782
|View full text |Cite
|
Sign up to set email alerts
|

Routledge Handbook of the Study of the Commons

Abstract: The "commons" has come to mean many things to many people, and the term is often used inconsistently. The study of the commons has expanded dramatically since Garrett Hardin's The Tragedy of the Commons (1968) popularized the dilemma faced by users of common pool resources.This comprehensive Handbook serves as a unique synthesis and resource for understanding how analytical frameworks developed within the literature assist in understanding the nature and management of commons resources. Such frameworks include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 583 publications
(834 reference statements)
0
4
0
Order By: Relevance
“…Ostrom (1990Ostrom ( , 2010 demonstrated that local, self-organized communities have long established institutional arrangements to sustainably manage 'common-pool resources' (CPR) without resorting to government regulation or privatization. A next generation of scholars has expanded on Ostrom's findings to apply her principles to different types of commons, including urban commons (Foster & Iaione, 2016), knowledge commons (Madison et al, 2009), and global commons (Hudson et al, 2019).…”
Section: From Commons To Commoningmentioning
confidence: 99%
“…Ostrom (1990Ostrom ( , 2010 demonstrated that local, self-organized communities have long established institutional arrangements to sustainably manage 'common-pool resources' (CPR) without resorting to government regulation or privatization. A next generation of scholars has expanded on Ostrom's findings to apply her principles to different types of commons, including urban commons (Foster & Iaione, 2016), knowledge commons (Madison et al, 2009), and global commons (Hudson et al, 2019).…”
Section: From Commons To Commoningmentioning
confidence: 99%
“…605-606, emphasis added). These promoted commons might be actual commons that are "co-opted" for commodity production, or I argue, they may be "pseudo-commons" as well (Theesefeld, 2019). Pseudo-commons occur when institutions create "initiatives that use the notion of commons and a blueprint of a common-property regime in an artificial nutshell," but commoning relations do not actually function on the ground (Theesefeld, 2019, p. 346).…”
Section: Commoning Versus Pseudo-commoning and The Commons' Capitalist Stancementioning
confidence: 99%
“…Drawing from the concept of capital fixes (De Angelis, 2013), pseudo-commons (Theesefeld, 2019), and Gibson-Graham et al's (2016) definition of commoning as a "relational process . .…”
Section: Pseudo-commoning As a Capitalist Fixmentioning
confidence: 99%
See 1 more Smart Citation